Cytoarchitectonic mapping of attentional selection and reorienting in parietal cortex. - Gillebert, C; Mantini, D; Peeters, R; Dupont, P; Vandenberghe, R (Elsevier, 2013)
Selection and reorienting are two fundamental aspects of spatial attention. By means of event-related fMRI in a total of 26 subjects, we localised these two processes within a same experiment applying a probabilistic cytoarchitectonic reference frame.In a classical spatial cueing paradigm, the target was presented at the cued location either alone (60% of trials) or in combination with a contralateral distracter ('competition trials', 20% of trials), or at a location opposite to the cued location ('invalidly cued trials', 20% of trials). In a sensory control experiment we differentiated between the attentional and the sensory effects of the distracter. In areas hIP1 and hIP3, competition trials exerted a significantly stronger attentional effect than invalidity trials. Conversely, area PF in the right hemisphere showed an invalidity effect in the absence of competition effect. A third type of response was found in areas PFm and PGa which showed both an invalidity and a competition effect. The combined study of selection and reorienting using a cytoarchitectonic reference frame enabled us to resolve the wide between-study variance in temporoparietal coordinates associated with the invalidity effect. Furthermore, the study demonstrated within a same experiment a functional dissociation between reorienting and selection in parietal cortex.